Event Carnival sebagai Media Komunikasi Pemasaran: Studi Kasus di SMA PKP JIS - Yayat Wahyat Herianto; Irwansyah Irwansyah (MediaTor (Jurnal Komunikasi), 2019)
This study aims to introduce an event in educational institution by adopting cultural event that was rife in Indonesia such as Jember Fashion Carnaval. The event which was named Carnival based on research has shown results. (1) Event carnival can improve the school brand, (2) Event Carnival activities that were attended by many junior and senior high schools indicated the formation of a network society, (3) event which were based on local wisdom and culture was infrequently  done in schools.  (4 ) Carnival event for PKP JIS High School was part of marketing communication that was important in the context of school promotion. This study uses a qualitative design with a case study approach. The data is carried out through observations, interviews and documentation studies